A Green Analytical Method Using Ultrasound in Sample Preparation for the Flow Injection Determination of Iron, Manganese, and Zinc in Soluble Solid Samples by Flame Atomic Absorption Spectrometry - M. Carmen Yebra (Journal of Analytical Methods in Chemistry)
A simple and rapid analytical method was developed for the determination of iron, manganese, and zinc in soluble solid samples. The method is based on continuous ultrasonic water dissolution of the sample (5–30 mg) at room temperature followed by flow injection flame atomic absorption spectrometric determination. A good precision of the whole procedure (1.2–4.6%) and a sample throughput of ca. 25 samples h–1 were obtained. The proposed green analytical method has been successfully applied for the determination of iron, manganese, and zinc in soluble solid food samples (soluble cocoa and soluble coffee) and pharmaceutical preparations (multivitamin tablets). The ranges of concentrations found were 21.4–25.61 μg g-1 for iron, 5.74–18.30 μg g-1 for manganese, and 33.27–57.90 μg g-1 for zinc in soluble solid food samples and 3.75–9.90 μg g-1 for iron, 0.47–5.05 μg g-1 for manganese, and 1.55–15.12 μg g-1 for zinc in multivitamin tablets. The accuracy of the proposed method was established by a comparison with the conventional wet acid digestion method using a paired t-test, indicating the absence of systematic errors.